2016
DOI: 10.1371/journal.pone.0147666
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Adaptation of Rotaviruses to Tumor Cell Lines

Abstract: A number of viruses show a naturally extended tropism for tumor cells whereas other viruses have been genetically modified or adapted to infect tumor cells. Oncolytic viruses have become a promising tool for treating some cancers by inducing cell lysis or immune response to tumor cells. In the present work, rotavirus strains TRF-41 (G5) (porcine), RRV (G3) (simian), UK (G6-P5) (bovine), Ym (G11-P9) (porcine), ECwt (murine), Wa (G1-P8), Wi61 (G9) and M69 (G8) (human), and five wild-type human rotavirus isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 73 publications
(71 reference statements)
3
25
0
2
Order By: Relevance
“…Rotavirus isolates Wt1-5, WWM, TRUYO, ECwt-O, and WTEW, selected as previously reported 36 , were trypsin-activated (10 mg/ml) and separately inoculated (MOI of 2) in Sp2/0-Ag14 cells (1 x 10 7 ) in DMEM (10 ml) without FBS. The cells were cultured at 37 °C until their lysis (about 24 h).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rotavirus isolates Wt1-5, WWM, TRUYO, ECwt-O, and WTEW, selected as previously reported 36 , were trypsin-activated (10 mg/ml) and separately inoculated (MOI of 2) in Sp2/0-Ag14 cells (1 x 10 7 ) in DMEM (10 ml) without FBS. The cells were cultured at 37 °C until their lysis (about 24 h).…”
Section: Methodsmentioning
confidence: 99%
“…ELISA analyses were conducted as previously described 36 . Briefly, Sp2/0-Ag14 cells were separately infected with the rotavirus isolates described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the team of Guerrero et al (32) has reported similar results on the oncolytic properties of rotavirus against several cancer lines although with reduced potency compared to our results. We examined cells after 24 hours or more instead of 12 hours and also used strains selected for commercial vaccines, which were not the same as the Guerrero et al (32) study.…”
Section: It Rotavirus With S Y S T E M I C a N T I -C T L A -4 Genementioning
confidence: 99%
“…GM-CSF: Factor estimulador de colonias monocito-macrófago; NSCLC: cáncer de pulmón de células no pequeñas; RGD: Arg-Gly-Asp motif; TK: timidina quinasa; US11: glicoproteína corta única 11. En el Laboratorio de Biología Molecular de Virus de la Facultad de Medicina de la Universidad Nacional de Colombia se han realizado estudios en los cuales se encontró que cepas rotavirales aisladas en el laboratorio infectan y lisan las líneas celulares Sp2/0-Ag14 cells (mieloma de ratón), U-937 (linfoma histiocítico), REH (leucemia linfocítica aguda), Kato III (carcinoma gástrico), MCF-7 (adenocarcinoma de mama), PC-3 (adenocarcinoma grado IV de próstata) y A549 (carcinoma de pulmón humano), lo que sugiere que las cepas estudiadas son potenciales virus oncolíticos (18).…”
Section: Virus Oncolíticosunclassified